Peculiarities of Stark-phonon Resonance in Two-dimensional Superlattices with Non-additive Energy Spectrum - D.V. Zav’yalov; S.V. Kruchkov; E.S. Ionkina (Журнал нано- та електронної фізики)
Current density in two-dimensional superlattice with non-additive energy spectrum placed in quantizing electric field has been calculated. The calculations were performed by taking into account an inelastic scattering of charge carriers by optical phonons. It is shown that the current-voltage characteristic is a series of peaks corresponding to Stark-phonon resonance.